2018
DOI: 10.1038/s41386-018-0277-4
|View full text |Cite
|
Sign up to set email alerts
|

VGF and its C-terminal peptide TLQP-62 in ventromedial prefrontal cortex regulate depression-related behaviors and the response to ketamine

Abstract: Patients with major depressive disorder (MDD) often have structural and functional deficits in the ventromedial prefrontal cortex (vmPFC), but the underlying molecular pathways are incompletely understood. The neuropeptide precursor VGF (non-acronymic) plays a critical role in depression and antidepressant efficacy in hippocampus and nucleus accumbens, however its function in vmPFC has not been investigated. Here, we show that VGF levels were reduced in Brodmann area 25 (a portion of human vmPFC) of MDD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 67 publications
1
38
0
Order By: Relevance
“…Derepressed VGF expression from the deep layer may have functions separate from CIC-mediated neuronal differentiation and maturation. Corroborating this possibility, a recent study demonstrated that VGF has a critical role in mood regulation (37,38).…”
Section: Discussionmentioning
confidence: 98%
“…Derepressed VGF expression from the deep layer may have functions separate from CIC-mediated neuronal differentiation and maturation. Corroborating this possibility, a recent study demonstrated that VGF has a critical role in mood regulation (37,38).…”
Section: Discussionmentioning
confidence: 98%
“…The Vgf (non-acronymic) gene encodes a neuronal and neuroendocrine protein precursor [1] that is posttranslationally processed with cell-and tissue-type specificity into multiple bioactive peptides that are secreted and are involved in numerous physio/pathological functions including reproduction [2], depression [3,4], obesity [5], memory [6] and also neurodegenerative diseases, in particular Alzheimer's disease (AD). In AD patients, VGF-derived peptides are reduced in the cerebrospinal fluid (CSF), suggesting their potential utility as biomarkers and a possible role for VGF in AD pathogenesis and progression [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The neuropeptide precursor VGF plays a pivotal role in the etiology of depression and antidepressant action [ 66 ]. Research studies have shown that the levels of VGF were decreased in BA25 (a part of human vmPFC) of MDD individuals and in the vmPFC of mice which experienced CRS training, while they were elevated by ketamine in mice vmPFC [ 66 ].…”
Section: Major Molecular Mechanism Of the Pfc During Depressionmentioning
confidence: 99%
“…The neuropeptide precursor VGF plays a pivotal role in the etiology of depression and antidepressant action [ 66 ]. Research studies have shown that the levels of VGF were decreased in BA25 (a part of human vmPFC) of MDD individuals and in the vmPFC of mice which experienced CRS training, while they were elevated by ketamine in mice vmPFC [ 66 ]. The overexpression of VGF in vmPFC rescued behavioral deficits induced by CRS, and the knockdown of VGF in vmPFC increased the susceptibility to subchronic variable stress (SCVS) and inhibited the antidepressant efficacy of ketamine [ 66 ].…”
Section: Major Molecular Mechanism Of the Pfc During Depressionmentioning
confidence: 99%